Novel Bovine Serum Albumin-Decorated-Nanostructured Lipid Carriers Able to Modulate Apoptosis and Cell-Cycle Response in Ovarian, Breast, and Colon Tumoral Cells - Robert Tincu; Mirela Mihaila; Marinela Bostan; Florina Teodorescu; Daniela Istrati; Nicoleta Badea; Ioana Lacatusu (MDPI AG, 2023)
A novel nanoscale approach was developed for the improved cellular internalization of hybrid bovine serum albumin-lipid nanocarriers loaded with piperine (NLC-Pip-BSA) in different tumor cells. The effect of the BSA-targeted-NLC-Pip and untargeted-NLC-Pip on the viability, proliferation, and levels of cell-cycle damage and apoptosis in the colon (LoVo), ovarian (SKOV3) and breast (MCF7) adenocarcinoma cell lines was comparatively discussed. NLCs were characterized concerning particle size, morphology, zeta potential, phytochemical encapsulation efficiency, ATR-FTIR, and fluorescence spectroscopy. The results showed that NLC-Pip-BSA showed a mean size below 140 nm, a zeta potential of −60 mV, and an entrapment efficiency of 81.94% for NLC-Pip and 80.45% for NLC-Pip-BSA. Fluorescence spectroscopy confirmed the coating of the NLC with the albumin. By MTS and RTCA assays, NLC-Pip-BSA showed a more pronounced response against the LoVo colon cell line and MCF-7 breast tumor cell lines than against the ovarian SKOV-3 cell line. Flow cytometry assay demonstrated that the targeted NLC-Pip had more cytotoxicity and improved apoptosis than the untargeted ones in MCF-7 tumor cells (p < 0.05). NLC-Pip caused a significant increase in MCF-7 breast tumor cell apoptosis of ~8X, while NLC-Pip-BSA has shown an 11-fold increase in apoptosis.